Barriers and opportunities of soil knowledge to address soil challenges: Stakeholders' perspectives across Europe. (1st January 2023) - Vanino, Silvia; Pirelli, Tiziana; Di Bene, Claudia; Bøe, Frederik; Castanheira, Nádia; Chenu, Claire; Cornu, Sophie; Feiza, Virginijus; Fornara, Dario; Heller, Olivier; Kasparinskis, Raimonds; Keesstra, Saskia; et al.
Abstract: Climate-smart sustainable management of agricultural soil is critical to improve soil health, enhance food and water security, contribute to climate change mitigation and adaptation, biodiversity preservation, and improve human health and wellbeing. The European Joint Programme for Soil (EJP SOIL) started in 2020 with the aim to significantly improve soil management knowledge and create a sustainable and integrated European soil research system. EJP SOIL involves more than 350 scientists across 24 Countries and has been addressing multiple aspects associated with soil management across different European agroecosystems. This study summarizes the key findings of stakeholder consultations conducted at the national level across 20 countries with the aim to identify important barriers and challenges currently affecting soil knowledge but also assess opportunities to overcome these obstacles. Our findings demonstrate that there is significant room for improvement in terms of knowledge production, dissemination and adoption. Among the most important barriers identified by consulted stakeholders are technical, political, social and economic obstacles, which strongly limit the development and full exploitation of the outcomes of soil research. The main soil challenge across consulted member states remains to improve soil organic matter and peat soil conservation while soil water storage capacity is a key challenge in Southern Europe. Findings from this study clearly suggest that going forward climate-smart sustainable soil management will benefit from (1) increases in research funding, (2) the maintenance and valorisation of long-term (field) experiments, (3) the creation of knowledge sharing networks and interlinked national and European infrastructures, and (4) the development of regionally-tailored soil management strategies. All the above-mentioned interventions can contribute to the creation of healthy, resilient and sustainable soil ecosystems across Europe. Highlights: Survey in 20 countries: 314 stakeholders, 10 soil challenges, 4 soil knowledge. Increasing organic matter and conserve peat soils is the priority soil challenge. The 2nd most important soil challenge is soil water storage capacity. The priority barriers are the lack of research funding and communication. The most important opportunity is to fully exploit the outcomes of soil research.